If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6k + -2 = 34 Reorder the terms: -2 + -6k = 34 Solving -2 + -6k = 34 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -6k = 34 + 2 Combine like terms: -2 + 2 = 0 0 + -6k = 34 + 2 -6k = 34 + 2 Combine like terms: 34 + 2 = 36 -6k = 36 Divide each side by '-6'. k = -6 Simplifying k = -6
| 9x-4x=5x-2 | | X/30=2 | | K/K^0.25 | | 3j-18=33 | | 5x-12=-52 | | 6=-3-x | | 4z-2x=18 | | udx+(1-3u)xdu=3u^2(e^3u)du | | 20-x/5=15 | | 9p+3=30 | | 42+5q=41 | | 5y-z=14 | | 12t^2-55t+90=0 | | 2x+8-7(x+1)=3x+8 | | 3.4n-9.2=-12.2+2.4n | | 7u+8=50 | | 6r+(-1)+6r=11 | | X+3x+6=0 | | 3-(2-3)= | | y-(2-y)= | | (8d-20)(8d-6)=0 | | X=0.5*(16-8y) | | (8x-20)(8d-6)=0 | | 6*x=64-2x | | 15/x-4=2/x | | 4x^2+18x=22 | | Sin(2x)tan(x)-tan(x)=0 | | 2^n=5/4 | | knx=3/2 | | k(x)=2f(-2x)-1 | | 5(x-2)=12x | | 4+6n=10 |